Modified Allen Test Assessment via Imaging Photoplethysmography - Kossack Benjamin; Wisotzky Eric L.; Schraven Sebastian; Skopnik Lotte; Hilsmann Anna; Eisert Peter (Current Directions in Biomedical Engineering, 2023)
The modified Allen test (MAT) is a widely used tool to examine the perfusion capacities of the arteries (ulnar or radial) of the hand. In clinical practice, MAT is utilized to ensure that in the event of occlusion, remaining vessels guarantee sufficient hand perfusion. This work shows that perfusion assessment via imaging photoplethysmography (iPPG) can be used to assess MAT. We captured the hands of seven subjects with a standard RGB camera while performing a MAT. Out of these captured video recordings, the iPPG signal was extracted via plane-orthogonal-to-skin transformation. Based on these extracted signals, we derive the heart rate, signal-to-noise ratio, DC parameter, and correlation with a reference iPPG signal to determine if an Allen test was pathological or inconspicuous. For all seven subjects, the results of our MAT assessment were identical to the medical expert’s assessment. This paper presents a procedure and initial thresholds for objectively evaluating and quantifying MAT.We show how globally and locally calculated parameters can be used to assess the perfusion of the investigated hand. This analysis makes it possible to quantify the exact point in time when the perfusion is again sufficient. If a reperfusion problem occurs, we are able to localize the spatial regions of occurrence. The presented hardware setup is affordable and can be easily installed and used in every doctor’s office.